Circulating plasmablasts and follicular helper T-cell subsets are associated with antibody-positive autoimmune epilepsy - Hara, Atsushi; Chihara, Norio; Akatani, Ritsu; Nishigori, Ryusei; Tsuji, Asato; Yoshimura, Hajime; Kawamoto, Michi; Otsuka, Yoshihisa; Kageyama, Yasufumi; Kondo, Takayuki; Leypoldt, Frank; Wandinger, Klaus-Peter; et al. (Frontiers in Immunology, 2022)
Abstract Autoimmune epilepsy (AE) is an inflammatory disease of the central nervous system with symptoms that have seizures that are refractory to antiepileptic drugs. Since the diagnosis of AE tends to rely on a limited number of anti-neuronal antibody tests, a more comprehensive analysis of the immune background could achieve better diagnostic accuracy. This study aimed to compare the characteristics of anti-neuronal antibody-positive autoimmune epilepsy (AE/Ab(+)) and antibody-negative suspected autoimmune epilepsy (AE/Ab(-)) groups. A total of 25 patients who met the diagnostic criteria for autoimmune encephalitis with seizures and 11 healthy controls (HC) were enrolled. All patients were comprehensively analyzed for anti-neuronal antibodies; 15 patients were identified in the AE/Ab(+) group and 8 in the AE/Ab(-) group. Differences in clinical characteristics, including laboratory and imaging findings, were evaluated between the groups. In addition, the immunophenotype of peripheral blood mononuclear cells (PBMCs) and CSF mononuclear cells, particularly B cells and circulating Tfh (cTfh) subsets, and multiplex assays of serum and CSF were analyzed using flow cytometry. Patients with AE/Ab(+) did not show any differences in clinical parameters compared to patients with AE/Ab(-). However, the frequency of plasmablasts within PBMCs and CSF in patients with AE/Ab(+) was higher than that in patients with AE/Ab(-) and HC, and the frequency of cTfh17 cells and inducible T-cell co-stimulator (ICOS) expressing cTfh17 cells within cTfh subsets was higher than that in patients with AE/Ab(-). Furthermore, the frequency of ICOShighcTfh17 cells was positively correlated with that of the unswitched memory B cells. We also found that IL-12, IL-23, IL-6, IL-17A, and IFN-γ levels were elevated in the serum and IL-17A and IL-6 levels were elevated in the CSF of patients with AE/Ab(+). Our findings indicate that patients with AE/Ab(+) showed increased differentiation of B cells and cTfh subsets associated with antibody production. The elevated frequency of plasmablasts and ICOS expressing cTfh17 shift in PBMCs may be indicative of the presence of antibodies in patients with AE.